The influence of coagulation and inflammation research on the improvement of polytrauma care. - Perl, M.; Huber-Lang, M.; Gebhard, F. (European Journal of Trauma & Emergency Surgery, 2012)
Treatment guidelines and management principles of polytrauma patients are largely derived from experience, supplemented by the results of few clinical studies. Their clinical impact on survival outcome is rarely scientifically evaluated. Hence, research algorithms need to be developed which enable a rapid and profound reevaluation of the current treatment strategies in polytrauma care and which provide a solid basis for the assessment of future treatment options. Such new concepts might include a more individualized approach and a better identification of operative windows for early definitive care. Since polytrauma results in a complex physiological and immunological disorder, which is additionally influenced by multiple confounding variables, it is challenging to establish such novel algorithms by clinical research only. In this regard, the well defined parameters in valid basic science models can provide a solid base for evaluating current concepts and investigating future treatment options. Here we have analyzed the contribution of basic science to well-established concepts in polytrauma care, such as the management of trauma induced coagulopathy or the damage control orthopedics concept. Many of these ideas moved from previous basic science activities to clinical studies but in many cases the direct effects of basic science on clinical trials or even clinical management strategies often remain elusive. Nevertheless, the knowledge which is created on a daily basis by basic science studies acts as an invaluable data pool, which can be accessed and combined for the clinical researcher to develop and address clinically relevant questions, providing them with a comprehensive pool of information to carefully plan and conduct their clinical trials. This may then subsequently lead to the development of new management principles for polytrauma patients.